2016
DOI: 10.1017/s0007114516001987
|View full text |Cite
|
Sign up to set email alerts
|

Combinational effects of prebiotic oligosaccharides on bifidobacterial growth and host gene expression in a simplified mixed culture model and neonatal mice

Abstract: It is important to provide formula-fed infants with a bifidobacteria-enriched gut microbiota similar to those of breastfed infants to ensure intestinal health. Prebiotics, such as certain oligosaccharides, are a useful solution to this problem, but the combinational benefits of these oligosaccharides have not been evaluated. This study investigated the benefits of oligosaccharide combinations and screened for an optimal combination of oligosaccharides to promote healthy gut microbiota of formula-fed infants. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Regarding other babies, we could not retrieve detailed information of formula milk consumed. Nevertheless, our data concurs with recent reports 40 , 48 , 49 suggesting that prebiotic-enriched formula may shift the microbiota of breast-fed babies towards a bifidobacteria-enriched configuration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding other babies, we could not retrieve detailed information of formula milk consumed. Nevertheless, our data concurs with recent reports 40 , 48 , 49 suggesting that prebiotic-enriched formula may shift the microbiota of breast-fed babies towards a bifidobacteria-enriched configuration.…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned previously, most infant-formula supplements presently prevalent in Japan contain prebiotic compounds such as galacto-oligosaccharides, fructo-oligosaccharides, etc. (concentration varying from 0.3 to 2.3% depending on the brand) that are known to augment the growth of bifidobacteria 47 , 48 . In our study, about 77% of mixed-fed infants were confirmed to be taking formula-feed fortified with galacto- or fructo-oligosaccharides, lactulose, or raffinose.…”
Section: Discussionmentioning
confidence: 99%
“…They are generally not digested to provide a neonate’s energy metabolism but are instead thought to control colonisation by pathogens through interfering with their sugar-based adhesion mechanisms required for binding to mucus layers or cell surfaces 7 , 61 . Milk oligosaccharides also play a crucial role in establishing an appropriate microbiome by, for instance, acting as a selective nutrient supply for species of Bifidobacterium 7 , 62 , 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Combinatorial benefits of various oligosaccharides are also beginning to be assessed, which may lead to the identification of optimal levels and combinations of prebiotics for the promotion of healthassociated bacteria in the gut. 93…”
Section: Oligosaccharidesmentioning
confidence: 99%